Rising house prices in an open labour market - Duffy, David; Fitz Gerald, John D.; Kearney, Ide (Economic & Social Studies, 2005)
We explore the consequences of rising house prices for the openness of the Irish labour market. Since many immigrants are in the household formation age group, and tend to be highly skilled, we argue that the boom in house prices, by reducing the attractiveness of Ireland for potential immigrants, could reduce labour supply. Using a structural model of the labour market we endogenise the determination of house prices. Our results suggest that rising house prices, by discouraging potential migrants, could significantly reduce the growth potential of the economy, shifting the balance of labour market growth from employment to wages, with a consequent deterioration in competitiveness.
Keywords: Housing market; Labour market; Ireland; House prices